Methods of Increasing the Reliability of the Received Data of the Photon Counter Based on the Analysis of the Pulse Counting Rate During the Transmission of Binary Symbols «0» - A. M. Timofeev (Приборы и методы измерений)
When measuring low-power optical signals, the receiving modules of systems should ensure a sufficiently high accuracy of the received data. In this regard, it is advisable to use photon counters. They are highly sensitive, but are characterized by data recording errors. The aim of this work was to determine the effect of the average pulse count rate of photons at the output of the counter on the reliability of the received information with the dead time photon counter.An expression for estimating the reliability of the received binary data when they were registered in the fiber-optic communication channel was obtained. This expression takes into account the statistical distributions of the number of pulses at the output of the photon counter.Studies have shown that with increasing ns0, the reliability of the data obtained at the beginning is practically does not change and is close to unity, and then decreases. Moreover, all other parameters being equal, with an increase in the average duration of the dead time of the prolonging type τd , this dependence decreases with large values of ns0: with ns0 ≥ 66,6·103 s-1 for τd = 0; with ns0 ≥ 74,1·103 s-1 for τd = 5 μs; with ns0 ≥ 83,5·103 s-1 for τd = 10 μs; with ns0 ≥ 95,6·103 s-1 for τd = 15 μs.